Comparison Of Two Countries (Bolivia And Australia) Based On Governance Indicators - Fakhrur Rodzi, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2024)
This article aims to discuss/analyse the comparison of governance between Australia and Bolivia based on six (6) indicators from the Worldwide Governance Indicators (WGI) by looking at the level of participation or public voice, political stability, against violence, rule of law, quality of regulations, government effectiveness and with how the level of corruption in the two countries This research includes library research with an analytical descriptive qualitative approach. The results of this study show that Australia has higher rankings in various governance indicators, such as public voice and accountability, politics and violence, quality of rules, rule of law, and control over corruption. Australia demonstrates greater political stability, higher quality of rule of law, and more effective controls on corruption. In contrast, Bolivia experienced challenges in terms of political instability and higher levels of violence. Despite improvements in Bolivia, the country still ranks lower than Australia in almost all aspects of governance